An Empirical Examination of Accounting Comparability: Goodwill Recognition and Disclosure in Selected Central European Countries - Ewa Wanda Maruszewska; Marzena Strojek-Filus; Jiří Pospíšil (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2019)
Over the last few decades, there have been unusually frequent changes in the required accounting rules and methods for measuring and reporting positive and negative goodwill of business entities and capital groups. We suggest that the lack of consistent accounting regulations among Central Eastern European countries in accounting for positive and negative goodwill distorts the economic content of this very important economic resource and therefore its usefulness for decision making is adversely affected. The aim of this study is to investigate accounting regulations for goodwill in Poland, the Czech Republic, and Slovakia. To achieve this goal, a critical analysis of the literature is conducted, and the applicable legal regulations are analysed. An empirical case study regarding goodwill recognition, measurement, and disclosure is presented based on data received from an actual acquisition transaction. Since the three countries studied are neighbours and cross-country acquisitions are important instruments for regional economic development, we issue a call for regional harmonization of local accounting regulations, preferably based on International Financial Reporting Standards (IFRS).